Development of the Human Arterial Valves: Understanding Bicuspid Aortic Valve - Henderson, Deborah J.; Eley, Lorraine; Turner, Jasmin E.; Chaudhry, Bill (Frontiers in Cardiovascular Medicine, 2022)
Abnormalities in the arterial valves are some of the commonest congenital malformations, with bicuspid aortic valve (BAV) occurring in as many as 2% of the population. Despite this, most of what we understand about the development of the arterial (semilunar; aortic and pulmonary) valves is extrapolated from investigations of the atrioventricular valves in animal models, with surprisingly little specifically known about how the arterial valves develop in mouse, and even less in human. In this review we summarise what is known about the development of the human arterial valve leaflets, comparing this to mouse where appropriate.